Numerical Study of Laminar Heat Transfer in Baffled Square Channel with Various Pitches - Withada Jedsadaratanachai; Supattarachai Suwannapan; Pongjet Promvonge (My University, 2011)
The article presents a numerical analysis of laminar periodic flow and heat transfer characteristics in a constant temperature-surfaced square channel mounted with 30° angled baffles of various pitches. The computations were based on a finite volume method and the SIMPLE algorithm implemented. The fluid flow and heat transfer characteristics are presented for Reynolds number based on the channel hydraulic diameter ranging from 100 to 2000. The angled baffles were placed repeatedly on the lower and upper channel walls with in–line arrangement to generate a pair of streamwise counter–rotating vortex flows. Effects of different pitch ratios (PR = P/H) with a single baffle height ratio of 0.2 on heat transfer and pressure loss in the channel were examined. The baffled channel flow showed a fully developed periodic flow profile at about x/D≈7. The computation revealed that the pair of vortex flows created by the baffles exists and induces impingement/attachment flows on a side and the upper and lower walls leading to substantial increase in heat transfer rate over the test channel. The decrease in the PR led to the rise of friction factor only. The result showed that the optimum thermal performance enhancement factor of about 3.78 is found at PR = 2.5.
Keywords: Baffle; Hydraulic diameter; Heat transfer enhancement; Heat Transfer Mechanisms